Q: Simplify: 4(3 – x) – 3(-5 – 12x)

A: 4(3 – x) – 3(-5 – 12x) = 12 - 4x + 15 + 36x = 32x + 27

Question

Asked 2/20/2011 6:06:39 PM

Updated 41 days ago|5/14/2018 11:48:39 AM

1 Answer/Comment

Rating

3

4(3 – x) – 3(-5 – 12x)

= 12 - 4x + 15 + 36x

= 32x + 27

= 12 - 4x + 15 + 36x

= 32x + 27

Added 41 days ago|5/14/2018 11:48:39 AM

This answer has been confirmed as correct and helpful.

Solve by using PEMDAS: 6 X 3 + 10/2. **Weegy:**
6 X 3 + 10/2
= 18 + 10/2
= 18 + 5
= 23
(More)

Question

Expert Answered

Updated 7/16/2014 11:03:21 AM

1 Answer/Comment

solve by using PEMDAS: 6X3²X2/(5-2) WHICH IS THE CORRECT ANWSER OF THESE: 8 OR 10 OR 12 OR 14 OR NONE OF THE ABOVE
**Weegy:** 6X3²X2/(5-2) = 6x9x2/3 = 36, so that's none of the above. (More)

Question

Expert Answered

Updated 7/29/2014 10:39:38 PM

0 Answers/Comments

MULTIPLY:(5Xy4)(2x² y) wish is the correct anwer? 10x² y4, or 10x³ y 5, or 10x³ y4,or None of above?

Question

Not Answered

Updated 8/6/2014 6:37:35 AM

1 Answer/Comment

User: MULTIPLY:(5Xy4)(2x² y) wish is the correct answer? 10x² y4, or 10x³ y 5, or 10x³ y4, or7 x ³ y 5 None of above?
**Weegy:** 10x² y4 (More)

Question

Expert Answered

Updated 8/6/2014 5:27:09 AM

1 Answer/Comment

10x³ y 5 is the correct answer for :(5Xy4)(2x² y).

(5Xy4)(2x² y)

=5x*2x^2*y4*y

=10x^(1+2)*y^(4+1)

=10x^3y^5.

(5Xy4)(2x² y)

=5x*2x^2*y4*y

=10x^(1+2)*y^(4+1)

=10x^3y^5.

Added 8/6/2014 2:35:30 AM

This answer has been confirmed as correct and helpful.

Solve for x: -3x + 2 = 35wish is the correct answer is it:x = -11, or x = -37/3, or x = 33, or x = 11

Question

Not Answered

Updated 8/1/2014 3:17:36 PM

2 Answers/Comments

-3x + 2 = 35;

-3x = 35 - 2;

-3x = 33;

x = 33/-3;

x = -11

-3x = 35 - 2;

-3x = 33;

x = 33/-3;

x = -11

Added 8/1/2014 3:17:36 PM

This answer has been confirmed as correct and helpful.

27,014,448 questions answered

There are no comments.